Effects of Film-Bottomed Treatment on Absorbability and Translocation of Nitrogen in Spring Wheat in Arid Area - Zizhen Li; Xiaolei Zhou; Qing Tian; Low Pak Sum; Yuee Yan; Xujiao Zhou (Agronomy)
Plastic film-bottomed treatment (FBT) is a critical agricultural practice in arid regions, aimed at enhancing crop productivity by improving soil moisture retention and nutrient availability. However, the effects of different depths of film-bottomed treatment (DFBT) on nitrogen (N) absorption and translocation in spring wheat remain inadequately understood. We conducted a field experiment on sandy soil to investigate the effects of different DFBT depths (60, 70, 80, 90, and 100 cm) and on total N absorption amount (TNAA), total N translocation amount (TNTA) in all nutritive organs, grain nitrogen content (GN), and grain yield (GY). Morphological measurements included GY, GN, TNAA, and TNTA in the stem, sheath, leaf, spike axis, kernel husk (SAKH), and culm. The results showed that FBT significantly reduced soil moisture loss, with the 100 cm depth reducing soil leakage by 59.6% (p < 0.001). At the flowering stage, nitrogen derived from fertilizer (NDF) and soil nitrogen (NDS) were significantly higher at the 80 cm depth (p < 0.001). At maturity, the total nitrogen absorption amount (TNAA) and translocation amount (TNTA) in the main stem and across nutrient organs were significantly higher under the 80 cm DFBT (p < 0.001), leading to improved nitrogen use efficiency. The correlation between TNTA and GN was strongest at 80 cm (p < 0.001). Grain yield (GY) and GN were optimized at intermediate depths, particularly at 80 cm, suggesting this depth provides an optimal balance between water retention and drainage efficiency. These findings underscore the importance of optimizing DFBT depth, particularly at 80 cm, to achieve enhanced water retention, efficient nitrogen utilization, and improved crop productivity in arid agricultural systems. This research provides critical insights into sustainable agricultural practices under water-limited conditions, offering practical guidance for improving food security in arid regions.